A small molecule TrkB/TrkC neurotrophin receptor co-activator with distinctive effects on neuronal survival and process outgrowth. (November 2016) - Yang, Tao; Massa, Stephen M.; Tran, Kevin C.; Simmons, Danielle A.; Rajadas, Jayakumar; Zeng, Anne Y.; Jang, Taichang; Carsanaro, Sara; Longo, Frank M.
Abstract: Neurotrophin (NT) receptors are coupled to numerous signaling networks that play critical roles in neuronal survival and plasticity. Several non-peptide small molecule ligands have recently been reported that bind to and activate specific tropomyosin-receptor kinase (Trk) NT receptors, stimulate their downstream signaling, and cause biologic effects similar to, though not completely overlapping, those of the native NT ligands. Here, in silico screening, coupled with low-throughput neuronal survival screening, identified a compound, LM22B-10, that, unlike prior small molecule Trk ligands, binds to and activates TrkB as well as TrkC. LM22B-10 increased cell survival and strongly accelerated neurite outgrowth, superseding the effects of brain-derived neurotrophic factor (BDNF), NT-3 or the two combined. Additionally, unlike the NTs, LM22B-10 supported substantial early neurite outgrowth in the presence of inhibiting glycoproteins. Examination of the mechanisms of these actions suggested contributions of the activation of both Trks and differential interactions with p75 NTR, as well as a requirement for involvement of the Trk extracellular domain. In aged mice, LM22B-10 activated hippocampal and striatal TrkB and TrkC, and their downstream signaling, and increased hippocampal dendritic spine density. Thus, LM22B-10 may constitute a new tool for the study of TrkB and TrkC signaling and their interactions with p75 NTR, and provides groundwork for the development of ligands that stimulate unique combinations of Trk receptors and activity patterns for application to selected neuronal populations and deficits present in various disease states. Highlights: A TrkB/TrkC-activating compound, LM22B-10, has been identified and characterized. LM22B-10 promotes greater survival of neurons than native neurotrophins. LM22B-10 promotes more rapid neuritogenesis than native neurotrophins. LM22B-10 induces resistance to of neurite outgrowth to inhibitory glycoproteins. Alternative neurotrophic signaling patterns may be induced by non-classical ligands.